2023
DOI: 10.3390/ijerph20126170
|View full text |Cite
|
Sign up to set email alerts
|

The Beyond-Human Natural World: Providing Meaning and Making Meaning

Abstract: Much academic and media attention has been focused on how nature contributes to psychological health, yet, most of this focus has been on happiness or hedonic well-being. Although numerous writers and researchers have linked connecting with nature as a pathway to meaning in life, an integrated overview has not yet (to our knowledge) been offered. Our manuscript is thus of both theoretical and practical importance with respect to finding meaning in life. In this hybrid commentary/review paper, we examine the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…Indeed, as children and adults are confronted with the death of nature and the subsequent eco-anxiety it may generate, authors have suggested that being immersed in nature may help with gaining better knowledge of one's self-concept. This may help address existential threats that are provoked by climate change and foster meaning in life, namely through coherence with one's values (i.e., selfdetermined motivation) and overall purpose, appropriate to their developmental level (114). Furthermore, previous work on P4C and mental health brings us to conclude that when children are faced with existential questions, supporting them in reflecting and developing critical thinking skills about these questions improves their wellbeing and self-determination (107,108).…”
Section: Philosophy For Children (P4c) and Existential Psychologymentioning
confidence: 99%
“…Indeed, as children and adults are confronted with the death of nature and the subsequent eco-anxiety it may generate, authors have suggested that being immersed in nature may help with gaining better knowledge of one's self-concept. This may help address existential threats that are provoked by climate change and foster meaning in life, namely through coherence with one's values (i.e., selfdetermined motivation) and overall purpose, appropriate to their developmental level (114). Furthermore, previous work on P4C and mental health brings us to conclude that when children are faced with existential questions, supporting them in reflecting and developing critical thinking skills about these questions improves their wellbeing and self-determination (107,108).…”
Section: Philosophy For Children (P4c) and Existential Psychologymentioning
confidence: 99%
“…First, from a pure science perspective, it seems something quite fundamentally human about which we really should know a great deal. Second, from an applied perspective, and more pressingly, positive human-nature interactions have significant benefits for human health and well-being (including physical, psychological, and social dimensions; e.g., Barragan-Jason et al, 2023;Bratman et al, 2019;Hartig et al, 2014;Keniger et al, 2013;Lee et al, 2023;Luck et al, 2011;Marselle et al, 2021;McMahan & Estes, 2015;Oh et al, 2022;Passmore & Krause, 2023). Third, and also with significant practical implications, personalized ecologies are associated with human attitudes and behaviour towards nature (e.g., Alcock et al, 2020;Gaston et al, 2023;Pr evot et al, 2018;Richardson et al, 2020;Soga & Gaston, 2023a; personalized ecologies, because they are personal, may help thwart the 'compassion fade' that can hamper responses to large scale crises (Markowitz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A further context pertained to how meaning in life mediates or moderates negative emotion in the face of social unrest and the pandemic [15]. The natural environment was examined as another context wherein nature may play important roles in helping humans find coherence, significance, and purpose [16].…”
mentioning
confidence: 99%